Board governance in moderating the relationship between environmental performance and firm performance in Indonesia - Erfan Rachmadi; Jia Jia Hing (Sebelas Maret Business Review, 2024)
The results regarding the relationship between environmental performance and company performance are still inconclusive. This condition is because there is still confusion regarding what influences this relationship. This study examines the role of board governance (board size, independent board, and gender diversity), which corporate decisions are highly dependent on their governance. The sample used in this study covers 117 companies in Indonesia from 2015 to 2023, using panel data regression analysis. The results obtained from this study indicate that companies in Indonesia negatively influence environmental performance and company performance. Furthermore, we found that independent board and gender diversity moderate this relationship. This evidence can be attributed to the role of board governance in producing strategic decisions in its activities. Evidence of this moderating role significantly contributes to environmental and corporate performance literature. Finally, this study offers knowledge to policymakers and practitioners regarding the importance of the role of corporate boards in monitoring the performance of their company's management to make good business decisions.